Alkyne insertion into Cu–Al bonds and selective functionalization to form copper acyl compounds. Issue 59 (5th July 2022) - McManus, Caitilín; Crumpton, Agamemnon E.; Aldridge, Simon
Abstract : Insertion of alkynes into Cu–Al bonds can be controlled both stereo- and regioselectively, and the syn insertion products selectively derivatized by CO to give structurally characterized copper acyl complexes. Abstract : We report on the insertion of alkynes into heterometallic M–M′ bonds, producing (aluminylalkenyl)copper compounds which possess differential reactivity at the two derived M–C functions. Uniquely, this system is capable of controlling access to isolable syn or anti dimetallated alkenes, by employing either kinetic or thermodynamic control. Subsequent derivatization with CO is both stereoselective (to syn systems) and regioselective (to Cu–C bonds), leading to the formation of the first structurally characterized examples of copper acyl compounds - aided by the cooperative reactivity of the proximal aluminium centre.